DNA methylation markers in esophageal cancer - Xu, Yongle; Wang, Zhenzhen; Pei, Bing; Wang, Jie; Xue, Ying; Zhao, Guodong (Frontiers in Genetics, 2024)
Background: Esophageal cancer (EC) is a prevalent malignancy characterized by a low five-year survival rate, primarily attributed to delayed diagnosis and limited therapeutic options. Currently, early detection of EC heavily relies on endoscopy and pathological examination, which pose challenges due to their invasiveness and high costs, leading to low patient compliance. The detection of DNA methylation offers a non-endoscopic, cost-effective, and secure approach that holds promising prospects for early EC detection.To identify improved methylation markers for early EC detection, we conducted a comprehensive review of relevant literature, summarized the performance of DNA methylation markers based on different input samples and analytical methods in EC early detection and screening.Findings: This review reveals that blood cell free DNA methylation-based method is an effective noninvasive method for early detection of EC, although there is still a need to improve its sensitivity and specificity. Another highly sensitive and specific non-endoscopic approach for early detection of EC is the esophageal exfoliated cells based-DNA methylation analysis. However, while there are substantial studies in esophageal adenocarcinoma, further more validation is required in esophageal squamous cell carcinoma.In conclusion, DNA methylation detection holds significant potential as an early detection and screening technology for EC.